PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA MATERI VIRUS KELAS X SMA - Hanif, Septi Dianti; Fauziah, Yuslim; Arnentis, Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Virus material is one of the material that is closely related to the life and problems of everyday learners. This material is abstract so that it has difficulty level and problem complexity which is high enough. The purpose of this research is to produce a valid students worksheet based on Problem Based Learning (PBL) to increasing critical thinking skills on virus material. This research was conducted at the Laboratory of Biology Education Department of PMIPA FKIP University of Riau and Senior High School 8 Pekanbaru in March-July 2017. This type of research is a development research using 4D model conducted up to development stage. There are 3 students worksheet developed. The instruments of data collection in this research are students worksheet assessment / validation sheets, and student response questionnaires. After students worksheet was developed, validated by 4 validators and then tested I on 15 students Biology Education FKIP UR, and trial II on 20 students of Class XI in Senior High School 8 Pekanbaru. The validation result shows that the score of feasibility aspect of content of 3 LKPD developed is 4.02 valid categories, the mean score of design aspect is 4.00 valid categories, and the pedagogical aspect score is 3.88 valid categories. The average score of all aspects of the five LKPD is 3.96 valid categories. The results of the first test showed a mean score of 4.23 with very good category. The results of the second trial showed the average score of 4.02 with good category. The results of the answer analysis on trial II showed the average value of 92.75 with very good category. Students worksheet based Problem Based Learning (PBL) on virus material can increase understanding and knowledge about virus and can improve critical thinking ability of learners.Keywords: Development, LKPD, Problem Based Learning (PBL), Critical Thinking, Virus